Implementasi Peningkatan Hak Atas Tanah dari Hak Guna Bangunan Menjadi Hak Milik untuk Tanah Perumahan - Retno Sariwati; Ferry Anggriawan (Bhirawa Law Journal, 2022)
In Indonesia, there are still many people who cannot live in their houses because the status of the land is still a Building Use Right and its validity period has expired and is not renewed, so the owner cannot occupy his house if it is not upgraded. As is the case in one of the houses in a residential area in Madiun Regency, where not all of the land status has become property rights, but there are Building Use Rights and of course it will burden the owner of the residential house because if the validity period expires and is not extended. In accordance with the Decree of the Minister of Agrarian Affairs/Head of the National Land Agency Number 6 of 1998 concerning the Granting of Ownership Rights to Land for Residential Houses, it is stated that in order to guarantee housing, residents need to guarantee the continuity of rights to the land where they live and need to increase the granting of property rights to residential houses. whose land status is still Right to Build. The legal issue that will be analyzed in this research is how to implement an increase in land rights from Hak Guna Bangunan to Hak Milik for residential land in Indonesia.